Cognitive function in community-dwelling older people in central Taiwan - Hui-Chu Chuang; Shang-Chien Huang; Yu-Jung Chang; Po-Chun Hsieh; Yi-Wen Chiu (Tungs’ Medical Journal)
Background: With the increasing aging population, cognitive impairment in older individuals has become a social concern, making it a common health issue. Objectives: This study aimed to investigate the cognitive function of community-dwelling older individuals and subsequently explore the contributing factors. Methods: This was a cross-sectional study, including 150 individuals aged 65 years and older. The cognitive function was assessed using the Mini-Mental Status Examination (MMSE) and CogMate™. Descriptive and inferential statistical analyzes were performed using SPSS 24.0. Results: Most participants were female, accounting for 80%. The average age of the participants was 74.90 ± 6.60 years. Furthermore, 70% of the participants had an educational level of elementary school or below. Among the participants, 62% and 66.7% exhibited cognitive impairment based on the MMSE and CogMate™ assessments, respectively. Age, educational level, marital status, and health condition were common factors influencing the MMSE and CogMate™ scores. Conclusion: The prevalence of cognitive impairment is high among community-dwelling older individuals. The results of the MMSE and CogMate™ assessments were comparable. The cognitive function of community-dwelling older individuals should be regularly assessed to facilitate early detection and provide suitable medical care intervention and supportive counseling, thereby enhancing their quality of life.